High resolution dynamic electrostatic force microscopy technique: quantifying electrical properties at the nanoscale. Issue 1652 (12th March 2014) - Maragliano, C.; Heskes, D.; Stefancich, M.; Chiesa, M.; Souier, T.
Abstract: In electrostatic force microscopy (EFM), a conductive atomic force microscopy (AFM) tip is electrically biased against a grounded sample and electrostatic forces are investigated. This methodology has been broadly used in the scientific community to characterize dielectric properties of samples at the nanoscale. Two are the main operating conditions associated with this technique. The oscillation amplitude is usually kept to very small values to allow a linearized approach to the force reconstruction and the tip-sample distance is maintained elevated. However, this latter condition negatively affects the lateral resolution of the technique. Thus, electrostatic interaction should be probed in the vicinity of the sample. Theoretically, in this region the force can be linearized using oscillation amplitudes in the order of Å. This might cause the trapping of the tip on the surface (snap-in). Furthermore, at small distances, short-range forces (i.e. Van der Waals') might reach values comparable to electrostatic forces. Here we present a framework that combines EFM and dynamic amplitude modulation AFM to achieve decoupled reconstruction of forces. It permits reconstructing the real shape of the electrostatic force and the capacitance of the tip-sample system even in the vicinity of the surface. This is done using a technique proposed in literature by Sader and Katan to reconstruct the force without the linearization approximation. The steps needed to decouple short-range and electrostatic forces are explained in detail. This data can be employed to derive the electrical properties of thin films with enhanced lateral resolution with respect to the commonly used EFM techniques.